International trade cooperation's impact on the world economy - Jeanne Métivier; Marc Bacchetta; Eddy Bekkers; Robert Bernard Koopman (World Trade Organization (WTO), 2023)
In this study, we investigate three trade policy scenarios: i) the revival of multilateralism, ii) plurilateral cooperation, and iii) geopolitical rivalry. In the first scenario, both tariffs and NTMs are reduced on a multilateral basis. In the second scenario, varying groups of countries cooperate on specific topics, such as E-commerce and services. In the last scenario, two main blocks emerge: a Western block and an Eastern block. International cooperation breaks down between blocks, leading to an increase in tariffs and NTMs, with blocks of countries setting up their own set of rules. Our findings are based on simulations with the WTO Global trade Model which has a specific novel feature: the diffusion of ideas between countries as a by-product of trade. The simulations indicate that: (i) there is a lot at stake for global trade cooperation, with global real GDP increasing by 3.2% compared to the baseline under multilateral cooperation and decreasing by 5.4% under geopolitical rivalry; (ii) LDCs would gain the most from multilateralism (real GDP increases by 4.8%) due to technology spillover effects; (iii) under both "open" and "exclusive" plurilateral agreements on services, most regions are projected to gain, with larger gains to participants if the initiative is "open" than if it is "exclusive"; (iv) intermediate linkages in services sectors will be reinforced in all scenarios, except under geopolitical rivalry; (v) geopolitical rivalry leads to a 21 percentage points decrease in exports between Western and Eastern blocks from 46% to 25%; and (vi) the WTO has an important role to play in preserving a free trade environment for developing countries and LDCs. The simulations show that in a decoupling world, it would be essential for LDCs to continue trading with both Eastern and Western blocks.
Keywords: F13; F17; 330; Trade policy simulations; CGE modeling